Hydrodynamic optimisation of a horizontal-axis hydrokinetic turbine for the River Ganga using a semi-analytical approach - Kripal; Anoop Kanjirakat (International Journal of Sustainable Engineering, 2025)
This study explores the design and optimisation of a horizontal-axis hydrokinetic turbine tailored to the unique flow conditions of the Ganga River, addressing a critical gap in deploying such technologies within the Indian subcontinent. The novelty lies in a rigorous multi-stage methodology, site-specific flow analysis, comparative hydrofoil evaluation of predominantly used profiles, cavitation safety assessment, and exploration of a swept blade approach to enhance performance. The research aims to improve efficiency and maximise annual energy production by offering a sustainable, low-impact alternative to traditional hydroelectric systems, ultimately achieving an output of 3569 kWh/year. Among 20 hydrofoil candidates evaluated, the SG 6043 and NACA 63–818 were identified as optimal in terms of lift-to-drag performance. SG 6043 was selected based on superior cavitation resistance, an essential criterion in hydrokinetic turbine design. The turbine configuration was determined using a rotor optimisation tool integrating a genetic algorithm with a semi-analytical blade-element momentum theory. This enabled identification of an optimal configuration ensuring an efficient power curve while maintaining sufficient cavitation safety margin. Additionally, the investigation revealed that the swept blade design did not yield performance benefits under the given site-specific conditions.